Effects of D-penicillamine on growth and cell cycle kinetics of cultured rabbit articular chondrocytes. Issue 2 (April 1984) - Jaffray, P; Ronot, X; Adolphe, M; Fontagne, J; Lechat, P
Abstract : The long-acting antirheumatic drug D-penicillamine was found to inhibit the growth of asynchronous cultures of rabbit articular chondrocytes. This inhibitory effect was dose-related between 5 X 10(-4) M and 5 X 10(-3) M and was time-dependent for a given dose. Flow cytometric analysis showed that drug exposure led to a slowdown in cell cycle progression. This was manifested as a decrease in the number of cells in S phase, due especially to an accumulation of cells in G0 G1 and also to a slight cessation of cell transit through G2 M. Recovery experiments showed that the effect is transitory and reversible. It is suggested that the articular chondrocyte is a target cell for D-penicillamine and that these cells have a D-penicillamine sensitive restriction point in the G0 G1 phase of the cell cycle and to a less extent in the G2 M phase.